Public Values Program Kartu Pedagang Produktif (KPP) di Kabupaten Bojonegoro - Cantika Ariyanto; Ahmad Suprastiyo; Cahya Lukita (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study aimed to explain the public value of the Productive Trader Card (KPP) program in Bojonegoro. The research method utilized was descriptive qualitative analysis. The informants were determined through a purposive sampling strategy. Data were collected based on the results of interviews with the Head of the UM Bojonegoro Trade and Cooperatives Office, as well as business actors who already had and did not have a KPP. The collected data were analyzed using the Miles & Huberman technique, covering three stages: data reduction, display, and verifying/conclusion drawing. The theory applied in this study is Mark Moore's public value, which consists of legitimacy and support, operational capabilities, and substantial value. The study results explain that the KPP program has been running well regarding Mark Moore's public value theory, although several indicators have not been met. The first indicator is the lack of full support from the community regarding this program; this is related to the government's lack of socialization efforts. The second indicator is that digital technology that supports the program has not been met because the KPP creation service cannot be done online. The third indicator is that substantial value has not been achieved regarding culture and ecology.